2017
DOI: 10.1074/jbc.m117.790675
|View full text |Cite
|
Sign up to set email alerts
|

NleB/SseK effectors from Citrobacter rodentium, Escherichia coli, and Salmonella enterica display distinct differences in host substrate specificity

Abstract: Many Gram-negative bacterial pathogens use a syringe-like apparatus called a type III secretion system to inject virulence factors into host cells. Some of these effectors are enzymes that modify host proteins to subvert their normal functions. NleB is a glycosyltransferase that modifies host proteins with -acetyl-d-glucosamine to inhibit antibacterial and inflammatory host responses. NleB is conserved among the attaching/effacing pathogens enterohemorrhagic (EHEC), enteropathogenic (EPEC), and Moreover, strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 16 publications
5
80
1
Order By: Relevance
“…Although previous reports had suggested both TRADD and FADD were substrates of SseK1 [8, 9, 11], our data suggested that TRADD is the preferred substrate of SseK1, as we could not detect modification of FADD during S. Typhimurium infection. TRADD plays a key role in the activation of canonical NF-κB signaling leading to pro-inflammatory cytokine secretion (reviewed in [17, 18]) and programmed cell death via TNF induced apoptosis or necroptosis [19].…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Although previous reports had suggested both TRADD and FADD were substrates of SseK1 [8, 9, 11], our data suggested that TRADD is the preferred substrate of SseK1, as we could not detect modification of FADD during S. Typhimurium infection. TRADD plays a key role in the activation of canonical NF-κB signaling leading to pro-inflammatory cytokine secretion (reviewed in [17, 18]) and programmed cell death via TNF induced apoptosis or necroptosis [19].…”
Section: Discussioncontrasting
confidence: 96%
“…A number of reports have used in vitro experiments to identify possible substrates of SseK1 [8, 9, 11]. While these studies have demonstrated the ability of SseK1 to GlcNAcylate a given target, the approach is substrate specific and there requires knowledge of the potential targets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly after this report, another function of NleB in interfering with TNF RSC assembly was uncovered in two reports that showed that NleB transfers GlcNac on arginine residues in death domains in TRADD (Arg 235), FADD (Arg 117), and RIPK1 (Arg 603, based on homology) (40,41). The GlcNac moiety interferes with death domain oligomerization, preventing the assembly of the TNF death receptor complex as well as NF-B activation by TNF (40)(41)(42). This unique posttranslational modification prevents activation of necroptosis and NF-B-mediated transcription of downstream cytokines and chemokines (43).…”
Section: Effectors That Interfere With Adapter Assemblymentioning
confidence: 98%